2012
DOI: 10.1097/prs.0b013e318244220d
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results following Cranial Hydroxyapatite Prosthesis Implantation in a Large Skull Defect Model

Abstract: The hydroxyapatite prosthesis showed its osteoconductivity and good biocompatibility. A low rate of fibrous tissue formation and a high rate of bony regeneration were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…[47][48][49][50][51][52][53] To date, acceptable clinical results have been obtained but no suitable solutions have been found as yet for regenerating long and loadbearing bone segments: Indeed, the mechanical strength of a highly porous but ''disorganized'' scaffold is often insufficient in order to manage the in vivo stresses and physiological loadings. So far, the development of three-dimensional synthetic systems with hierarchical architecture have been limited by the currently available processing technology.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53] To date, acceptable clinical results have been obtained but no suitable solutions have been found as yet for regenerating long and loadbearing bone segments: Indeed, the mechanical strength of a highly porous but ''disorganized'' scaffold is often insufficient in order to manage the in vivo stresses and physiological loadings. So far, the development of three-dimensional synthetic systems with hierarchical architecture have been limited by the currently available processing technology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the microstructure can be completely controlled. In particular, porous HAP implants that have been manufactured artificially and that have so-called open pore structures have excellent bone conduction and sufficient physical strength (Martini et al, 2012). For these reasons, they are already currently used in orthopedics, plastic surgery, neurosurgery, and dentistry (Byrd and Hobar, 1993;Ikenuma et al, 1988;Pompili et al, 1998;Rahn, 1989;Salyer and Hall, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Despite the advantages, hydroxyapatite use has been limited because of its brittle nature, low tensile strength, and high infection rates (Table 1). Hydroxyapatite has demonstrated osteointegration in animal models; 19,21,26 however, there is not much evidence for osteointegration for humans in vivo. 9 Frassanito et al demonstrated that hydroxyapatite may break down into many fragments over time in vivo, and they also demonstrated extremely limited osteointegration that lacked lamellar organization.…”
Section: Hydroxyapatitementioning
confidence: 99%